New developments in fish amino acid nutrition: towards functional and environmentally oriented aquafeeds - Li, Peng; Mai, Kangsen; Trushenski, Jesse; Wu, Guoyao (Amino acids, 2009)
Recent evidence shows that some amino acids and their metabolites are important regulators of key metabolic pathways that are necessary for maintenance, growth, feed intake, nutrient utilization, immunity, behavior, larval metamorphosis, reproduction, as well as resistance to environmental stressors and pathogenic organisms in various fishes. Therefore, conventional definitions on essential and nonessential amino acids for fish are challenged by numerous discoveries that taurine, glutamine, glycine, proline and hydroxyproline promote growth, development, and health of aquatic animals. On the basis of their crucial roles in cell metabolism and physiology, we anticipate that dietary supplementation with specific amino acids may be beneficial for: (1) increasing the chemo-attractive property and nutritional value of aquafeeds with low fishmeal inclusion; (2) optimizing efficiency of metabolic transformation in juvenile and sub-adult fishes; (3) surpressing aggressive behaviors and cannibalism; (4) increasing larval performance and survival; (5) mediating timing and efficiency of spawning; (6) improving fillet taste and texture; and (7) enhancing immunity and tolerance to environmental stresses. Functional amino acids hold great promise for development of balanced aquafeeds to enhance the efficiency and profitability of global aquaculture production.